Perceptions of coaching success: an exploratory analysis of Czech coaches views on success - Crossan, W.; Bednar, M.; Quinn, R. (Physical Culture and Sport. Studies and Research, 2021)
A philosophical framework for success in coaching is established, upon which the results of 571 coaches` views of suc-cess in coaching is consequently evaluated. The coaches are Czech nationals from seven sports, who coach all age groups from U8 to adult professional teams, with length of experience ranging from 1 to 26 years (mean 7.1). Success definitions were coded and categorized before being analyzed across sport, age group coached, experience and licensing level. Hal-lowell`s success cycle is used as a standard of evaluation. Results were also assessed in terms of modern coaching philo-sophies. Overall, it was shown that the most common definition of success by coaches fell into the Sport Growth domain (31.7%), by which they primarily meant Player Development (20.6% of these coaches). The second most common do-main for defining success was Performance (28.2%), primarily defined in terms of Winning (15.5%). Emotional Growth (21.1%) and Personal Growth (7.6%), though emphasized in modern coaching philosophies, were largely undervalued by Czech coaches. Enjoyment, a key element of success from Aristotle to Seligman, and essential to Hallowell`s success cycle was evident in only a small number (5.6%) of the success definitions of coaches.